PENGEMBANGAN MODUL AJAR MATEMATIKA MATERI TRIGONOMETRI BERBASIS COGNITIVE LOAD THEORY UNTUK MEMINIMALISIR MATHEMATIC ANXIETY SISWA FASE E - Zahroh, Umy; Sutopo, Sutopo; Fitri, Devin Anggraeni (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to: 1) determine the process of developing teaching module, 2) determine the validity of teaching modules, 3) determine the practicality of teaching modules, and 4) determine the effectiveness of teaching modules. In general, the development of this CLT-based teaching module is to find out whether the taching module can minimize students’ mathematical anxiety.The research follows a development model, specifically the Plomp development model which consists of 5 phase, 1) preliminary phase, 2) design phase, 3) realization phase, 4) test, evaluation and revision phase, 5) implementation phase. The developed teaching module focuses on trigonometry material for phase E students at MAN Se-Tulungagung. Data collection methods include validation, objective observation, and questionnaires. Practicality data were obtained from teacher questionnaires, while effectiveness data were derived from students’ mathematical anxiety questionnaires. Based on data analysis, the following results were obtained: 1.) The validation score for the teaching module was 3.754, categorizing it as valid. 2.) The practicality score for the teaching module was 4.02, indicating high practicality. 3.) The teaching module effectively minimized mathematical anxiety, as evidenced by anxiety levels in experimental classes compared to control classes. Control classes using conventional learning showed higher anxiety levels, with MAN 3 Tulungagung at 2,89 (‘anxious’), MAN 2 Tulungagung at 2.615 (‘anxious’), and MAN 1 Tulungagung at 2.204 (‘anxious’). Meanwhile, experimental classes, after using the teaching module, showed lower anxiety levels: MAN 3 Tulungagung at 1.98 (‘moderate anxiety’), MAN 2 Tulungagung at 1.96 (‘moderate anxiety’), and MAN 1 Tulungagung at 1.44 (‘moderate anxiety’)